2020
DOI: 10.1088/1755-1315/454/1/012145
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sound treatment on phosphate solubilizing microbial activity

Abstract: Many soils have the problem of high phosphate retention values (> 85%) thus P is not available for plants. The activity of phosphate solubilizing microbes (PSM) is able to facilitate the availability of phosphorus in the soil. The ability of each microbe to dissolve inorganic phosphate varies and depends on the type of microbe and the microbial growth factors. In nature, almost all forms of life are surrounded by various types of sounds and they also interact with these sounds. Previous research found that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
1
0
Order By: Relevance
“…In addition, the results of a threeyear experiment on sound technology for rice production showed that acoustic technology could reduce the amount of fertilizer by about 25% (Hou et al, 2010). In accordance with research by (Munar et al, 2020) the application of sound affects the growth process of phosphate-dissolving microbes, as indicated by the discovery of phosphatedissolving fungi in the soil where sound is applied.…”
Section: Chlorophyll and Nutrient Contentsupporting
confidence: 62%
“…In addition, the results of a threeyear experiment on sound technology for rice production showed that acoustic technology could reduce the amount of fertilizer by about 25% (Hou et al, 2010). In accordance with research by (Munar et al, 2020) the application of sound affects the growth process of phosphate-dissolving microbes, as indicated by the discovery of phosphatedissolving fungi in the soil where sound is applied.…”
Section: Chlorophyll and Nutrient Contentsupporting
confidence: 62%
“…The quantity and activity of phosphate-solubilizing fungi gained influence from the soil's organic matter concentration as a source of energy and carbon (Deni et al, 2021). Besides, the research results by Munar et al (2020) reported that sound treatment affected the growth of phosphate-solubilizing microbes and all microbes that were not pathogenic to plants.…”
Section: Phosphate-solubilizing and Nitrogen-fixing Bacteria In Salin...mentioning
confidence: 99%